The Impact of Authority Relations and Feedback Delivery Method on Performance. Issue 1 (2nd April 2020) - Chae, Songhwa; Eagle, Lauren M.; Johnson, Douglas A.; Moon, Kwangsu; Choi, Eunju; Oah, Shezeen
ABSTRACT: The proliferation of technology has been changing feedback delivery methods in organizations. However, the effectiveness of feedback delivery methods can vary depending on social dynamics (e.g., authority relations) in the organization. The current study was designed to examine the impact of authority relations and feedback delivery methods on performance. A total of 120 participants were recruited to work on a simulated cell-phone assembly task and were exposed to one of the four feedback conditions: (a) authority figure with face-to-face feedback, (b) authority figure with e-mail feedback, (c) non-authority figure with face-to-face feedback, and (d) non-authority figure with e-mail feedback. Results showed that while both feedback delivery methods resulted in high performance with the presence of an authority figure, only face-to-face feedback resulted in high performance with a non-authority figure. Practical considerations for effective feedback delivery methods in relation to authority figures are also discussed.